The relationship between organizational learning and employee engagement: the perspective of young employees from commercial banks in Malaysia / Ibiwani Alisa Hussain, Noormala Amir Ishak and Benjamin Chan Yin Fah. - Hussain, Ibiwani Alisa; Amir Ishak, Noormala; Chan, Benjamin Yin Fah (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2016)
The purpose of the study is to investigate the relationship between organizational learning with employee engagement. Primary data were gathered through self-administered survey questionnaires. 100 respondents participated in the study and all of the respondents came from commercial bank in Malaysia. Method used to distribute the survey questionnaires was through "drop off and pick up" method due to the minimum interaction by the investigator with the respondents. Data were analyzed using SPSS and findings indicated that employees valued development opportunity provided by organisations for example development through training, mentoring and coaching. Respondents are employee between the age of 23 to 30 years old and these mode of learning appear to be the most effective to them.